KONTRIBUSI PELATIHAN GURU, IKLIM ORGANISASI DAN PERSEPSI GURU TENTANG KETERAMPILAN MANAJERIAL KEPALA SEKOLAH TERHADAP KETERAMPILAN GURU DALAM PEMBELAJARAN SMKN KOTA SEMARANG - Suparno, Aris (Universitas Muhammadiyah Surakarta, 2013)
The research?s goal is to know the contribution of teacher training, organization climate, and teacher perception about managerial skill of headmaster towards teacher skill in learning activity at SMK N in Semarang by simultant and partial. This research is including ex post facto qualitative research. The population in this research is SMK N teacher in Semarang counted 763 official state teachers (PNS) from 11 schools, with 5% guilty level so that the sample is 257 teachers. It is gain from Isaac and Michael table. In taking research sampling used sample random sampling. In this research, data collecting method used anquette or questionnaire. Data analysis technique is done by doubled linier regression with prerequisite test that is normality test, multicolinierity test, autocorrelation test and heterokedasticity test. Research?s result shows that (1) there is contribution of teacher training, organization climate, and teacher perception about managerial skill of headmaster towards teacher skill in learning activity at SMK N in Semarang by simultant, it is shown with significant value 0,000<0,05 with R2 counted 0,382 it means that teacher training, organization climate, and teacher perception about managerial skill of headmaster variables by together can explain teacher skill variable in learning counted 38,2% while the rest 61,8% is explain by another feature that is not researched. (2) there is contribution of teacher training towards teacher skill in learning activity at SMK N in Semarang, it is shown by significant value = 0,000 < 0, 05 with effective contribution that is given to teacher skill in learning activity counted 13,18%, (3) there is contribution of organization climate towards teacher skill in learning activity at SMK N in Semarang, it is shown by significant value = 0,000 < 0, 05 with effective contribution that is given to teacher skill in learning activity counted 16,87, and (4) there is contribution of teacher perception about managerial skill of headmaster towards teacher skill in learning activity at SMK N in Semarang, it is shown by significant value = 0,000 < 0, 05 with effective contribution that is given to teacher skill in learning activity counted 8,14%. Result of classical assumption test shows that regression model is not experience of classic assumption problem or diffraction, so that expressed BLUE (best, linear, unbiased, estimator. The Most Impact given by the organizational climate variables in learning skill teacher at SMK Negeri Semarang as indicated by an effective contribution amounting to 16,87 %.